Periarthritis of the Shoulder-MRI Findings - Nomura, Kazutoshi; Hashimoto, Noburo; Katahira, Kazuhiro; Hirano, Mako; Fukumoto, Tetsuya; Oshima, Suguru (Orthopedics & Traumatology, 1997)
We examined MRI findings in patients with periarthritis of the shoulder. We excluded cuff tears, calcified tendinitis, instability of the shoulder, fracture and impingement syndrome of young patients. Subjects camprised 36 cases, 38 shoulders(25 men and 11 women), with an average age of 59.1 years (42-75). Scanning was performed on a Gyroscan T5-II 0.5-T (Philips). T1-weighted and T2-weighted sequences in the coronal oblique plane, T2-weighted sequences in the coronal sagittal plane and horizontal plane were taken. Twelve shoulders showed some change in the humeral heads. Degeneration of the rotator cuff was observed in 15 shoulders. Joint fluid collection was observed in the gleno-humeral joints of 15 shoulders, in the subacromial bursa of 11 shoulders and in the acromio-clavicular joints of 7 shoulders. Twenty four shoulders had fluid collection in the sheath of the long head of the biceps long tendon. Localized high signal area was observed around the inferior pouch in 11 shoulders. We studied the relationship between MRI findings and clinical symptoms. There was no significant relationship but the shoulders with night pain and severe contractures had a higher positive rate of joint fluid collection on MRI than the shoulders without night pain and with less contractures.